2013
DOI: 10.1128/aem.03787-12
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Approach To Uncover the Low-Temperature Adaptation Strategies of the Archaeon Methanosarcina barkeri

Abstract: b Low-temperature anaerobic digestion (LTAD) technology is underpinned by a diverse microbial community. The methanogenic archaea represent a key functional group in these consortia, undertaking CO 2 reduction as well as acetate and methylated C 1 metabolism with subsequent biogas (40 to 60% CH 4 and 30 to 50% CO 2 ) formation. However, the cold adaptation strategies, which allow methanogens to function efficiently in LTAD, remain unclear. Here, a pure-culture proteomic approach was employed to study the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…This indicated that the cold adaptation of the two pathways may be at the mRNA level, namely, mtaA1 and mtaC1B1 expression was more cold adaptive than that of ackA and pta at the transcriptional level. A recent proteomics study (29) also showed the upregulation of the MtaC protein in the 15°C culture of Methanosarcina barkeri. mtaA1 and mtaC1B1 transcripts possessed high stabilities at both temperatures, while the pta-ackA transcript possessed reduced stability at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the cold adaptation of the two pathways may be at the mRNA level, namely, mtaA1 and mtaC1B1 expression was more cold adaptive than that of ackA and pta at the transcriptional level. A recent proteomics study (29) also showed the upregulation of the MtaC protein in the 15°C culture of Methanosarcina barkeri. mtaA1 and mtaC1B1 transcripts possessed high stabilities at both temperatures, while the pta-ackA transcript possessed reduced stability at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Species of Methanosarcina are metabolically versatile and can grow on methanol (+/ − H 2 ) or methylamines in addition to acetate or H 2 -CO 2 (Maestrojuán and Boone, 1991;Gunnigle et al, 2013). The ability to use different methanogenic substrates would be advantageous for Methanosarcina under the substrate limited conditions of peat.…”
Section: Active Archaeal Taxa In Anoxic Microcosmsmentioning
confidence: 99%
“…Recently, spectral counting, differential isotopic labelling strategies as well as label‐free quantitation were employed to study oxidative stress, the impact of individual mutations, or the exponential‐stationary growth phase transition, respectively, in Haloferax . Additional publications cover topics at the intersection of proteomics and the stress response for other archaea …”
Section: Introductionmentioning
confidence: 99%